Predicting in vivo phospholipidosis-inducing potential of drugs by a combined high content screening and in silico modelling approach. Issue 3 (April 2015) - Bauch, Caroline; Bevan, Samantha; Woodhouse, Heather; Dilworth, Clive; Walker, Paul
Highlights Two high content screening assays: phospholipidosis and lysosomal trapping. Validation of two cellular models: HepG2 and H9c2 cells. Applicability domains are required for compound classes like aminoglycosides. In vitro and in silico methods to predict phospholipidosis in vivo are compared. Formulation of a screening strategy to better predict phospholipidosis in vivo.